2019
DOI: 10.1111/area.12599
|View full text |Cite
|
Sign up to set email alerts
|

The primacy of anti‐blackness

Abstract: This paper contributes to conversations in Black Geographies by reflecting on the nature of anti-Black oppression. Much work within Black Geographies has (understandably and importantly) drawn out the ways in which race and class intersect with one another. This paper acknowledges the necessity of such an approach yet argues that scholars must be careful not to conflate anti-Black oppression with class-based oppression, as anti-Blackness is its own logic of oppression that eclipses class. I draw on three 20th-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Rather than suggesting that this difference is inherently cultural, Steffensmeier et al (2011) acknowledged important differences in these experiences as well, including the legacy of enslaving Africans and group differences in the degree of disadvantage (see also Light & Ulmer, 2016). In the same way that Bledsoe (2019) suggested that anti-Blackness is distinct from and surpasses class discrimination, the adversity that Black and Hispanic women and men face is different and appears to differentially influence their homicide risks. A prime example is racial/ethnic residential patterns for which the most extreme residential segregation, social isolation, and concentrated disadvantage—robust predictors of violence—are reserved for Black Americans, although this literature does not address racial/ethnic disadvantages at the intersection of gender (Charles, 2003; Iceland et al, 2002; Sampson & Wilson, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…Rather than suggesting that this difference is inherently cultural, Steffensmeier et al (2011) acknowledged important differences in these experiences as well, including the legacy of enslaving Africans and group differences in the degree of disadvantage (see also Light & Ulmer, 2016). In the same way that Bledsoe (2019) suggested that anti-Blackness is distinct from and surpasses class discrimination, the adversity that Black and Hispanic women and men face is different and appears to differentially influence their homicide risks. A prime example is racial/ethnic residential patterns for which the most extreme residential segregation, social isolation, and concentrated disadvantage—robust predictors of violence—are reserved for Black Americans, although this literature does not address racial/ethnic disadvantages at the intersection of gender (Charles, 2003; Iceland et al, 2002; Sampson & Wilson, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…In geography, racial capitalism has emerged as an important analytical thread within the emerging subfield of Black geographies (Bledsoe, 2020). Black geographies developed in response to a discipline that has willfully excluded the lives and experiences—the epistemologies and ontologies—of Black people and Black spatial processes (Bledsoe, 2021).…”
Section: Black Geographies and Racial Capitalismmentioning
confidence: 99%
“…She says, “As racial capitalism takes it out of people's hides, the contradiction of skin becomes clearer.” McKittrick (2016) extends this focus on the body to argue that racial capitalism refuses black humanity. Put another way, Bledsoe and Wright (2019) argue that the assumed absence of value in Black life makes global capitalism possible, and further that race is a condition of existence “that leads to premature death” (Bledsoe, 2020, p. 474). Taken together, geographers studying racial capitalism understand it as a system predicated on a racial hierarchy that deems Black people disposable.…”
Section: Black Geographies and Racial Capitalismmentioning
confidence: 99%
“…While many of the examples are drawn from North America, our analysis is intentionally porous and our framework open to adaptation to different contexts. The integration of public finance with intersectionality, Black geographies, and racial capitalism is not an intellectual project specific to North America (Hudson, 2018), nor should the public-private financial interface as we depict it here be understood as representative of all the ways it is configured elsewhere (but see Bledsoe, 2020). Future research in the directions we propose will undoubtedly benefit from an expanded selection of empirical sites and case studies.…”
Section: Public Finance In the Literaturementioning
confidence: 99%